Integrated Fungi Diversity from Kotok Bongkok, Bantens Traditional Food: Content for Innovative Teaching Materials in Senior High School Biology on Biodiversity - Mila Ermila Hendriyani; Sindanita Yulianti; Roswanna Safkolam; Rida Oktorida Khastini; Putri Dian Pramesty; Mariska Sandrina Oktaviani (Universitas Syiah Kuala, 2025)
Indonesia is very rich in traditional fermented foods, one of the distinctive foods from Banten that is still not widely known and scientifically studied is kotok bongkok. The study aims to integrate research results on fungal diversity in kotok bongkok as content for an innovative teaching material that senior high school students can use to study biology on biodiversity. The requirement for contextualized learning materials that connect complex biological ideas with students' real-world experiences served as the basis for the study. Four biology teachers were interviewed as part of a mixed-methods approach to get qualitative data, while 103 grade X students from three different schools completed questionnaires to gather quantitative data. Isolation and identification resulted in the identification of several fungal taxa in kotok bongkok, including Rhizopus oligosporus, Mucor racemosus, Rhizomucor pusillus, Penicillium sp., and yeast, which colonized kotok bongkok, providing authentic biological examples for learning fungal diversity. Both teachers and students see local food-based examples as viable and interesting teaching materials. While students preferred interactive media, including e-modules, videos, and learning applications, teachers highlighted the potential of project-based learning and module-based forms. The results were aligned with competencies to biotechnology, biodiversity, and the ecological roles of fungi, and matched to the learning objectives of Indonesia's merdeka curriculum. Kotok bongkok enriches the curriculum and encourages scientific literacy, cultural sensitivity, and sustainable knowledge practices in biology lessons. The work provides a reproducible strategy for contextualizing biology learning and highlights the pedagogical value of incorporating local knowledge into formal scientific education